The psychosocial dimensions of seborrheic dermatitis: A cross-sectional study on anxiety, personality, and quality of life - Gamze Taş Aygar; Hanife Karataş; Elif Kaya; Nur Şeyma Borazan; Selda Pelin Kartal (PLoS ONE, 2025)
Background Seborrheic dermatitis (SD) is a chronic inflammatory skin disorder that predominantly affects sebaceous gland-rich areas, such as the scalp, face, and chest. It is clinically characterized by erythematous plaques and scaling. Although its pathogenesis is multifactorial, involving genetic predisposition, microbial colonization, and environmental triggers, the psychosocial dimensions of SD remain insufficiently explored. Given the chronic and visible nature of the disease, psychological factors like anxiety and personality traits may shape patients’ perception of disease burden and their quality of life (QoL). Objectives This study aimed to assess the relationship between anxiety levels, personality traits, and the clinical severity and quality of life in patients with seborrheic dermatitis. By evaluating these dimensions together, the study seeks to better understand the psychosocial impact of SD. Materials and methods A cross-sectional study was conducted with 210 adult South Dakota patients. Disease severity was assessed using the Seborrheic Dermatitis Area and Severity Index (SDASI), while QoL was measured using the Dermatology Life Quality Index (DLQI). Anxiety was evaluated using the Beck Anxiety Inventory (BAI), and personality traits via the Bortner Personality Scale. Correlation analyses and regression models were employed. Results SDASI demonstrated a strong positive correlation with Physician Global Assessment (Rho = 0.815, p < 0.001), confirming its validity as a clinical severity tool. DLQI exhibited moderate positive correlations with both BAI and anxiety severity (Rho = 0.465 and Rho = 0.365, p < 0.001), indicating that anxiety substantially contributes to patient-perceived disease burden. In contrast, SDASI showed no significant associations with anxiety levels or personality traits (all p > 0.05), highlighting a dissociation between physician-rated severity and patient-reported quality of life. Weak correlations were observed between DLQI and female gender (Rho = 0.159, p = 0.011) as well as seasonality (Rho = 0.145, p = 0.018). Conclusion Seborrheic dermatitis imposes a significant psychosocial burden that is more strongly linked to anxiety than to objective clinical severity. Our findings underscore the importance of integrating routine psychological screening—such as BAI assessment—into SD management to identify patients at risk of diminished quality of life. This study contributes novel evidence by concurrently evaluating clinical, psychological, and personality dimensions, reinforcing the need for a multidimensional, patient-centered approach to chronic inflammatory skin disorders.